Curtin Sarawak accounting graduate receives MICPA award - Borneo Post, (Kuching) (Borneo Post (Kuching), 2016)
MIRI: Eleanor Wong Shi Ee, a Bachelor of Commerce (Accounting) graduate of Curtin University Sarawak is among 11 Malaysian graduates conferred the prestigious 2015 Malaysian Institute of Certified Public Accountants (MICPA) Excellence Award for Best Accounting Graduate.